Hybridasation Of Quality of Vaccine Services In Puskesmas In Rokan Hulu District - Taruna Taruna*; Rulinawaty Rulinawaty; Febri Yuliani (Universitas Syiah Kuala, 2023)
This research was conducted to comprehensively determine the quality of the Covid-19 vaccine service at the Public Health Center in Rokan Hulu Regency, hybridization of collaborations or partnerships between the government, the private sector and the community in the implementation of the Covid-19 19 vaccination services and the factors that hindered the Covid-19 vaccine service in Rokan Hulu Regency. This type of research is qualitative with a phenomenological approach which aims to obtain information by conducting in-depth interviews, observation and review of documents regarding the hybridization of the quality of Covid-19 vaccine services at the Public Health Center in Rokan Hulu Regency. The informants consisted of the Head of the Rokan Hulu Regency Health Office, the Head of the Rokan Hulu Regency Health Services Division, the Head of the Health Center, vaccinators, health promotion officers, sub-district heads, Headman, private sector and communities receiving vaccines. The triangulation used is the triangulation of sources, methods and data. Data analyzed by content analysis. The results of the research and discussion can be concluded that the quality of the Covid-19 vaccine service at the Public Health Center in Rokan Hulu Regency is generally good and in line with what the public expects. Hybridization between the government, the private sector and the community has been going well without any problems. Obstacles in the Covid-19 vaccination service, rejecting and doubting the vaccine, not continuing the vaccine to the next dose because there are no more restrictions on activities and the use of public facilities by the government such as being required to have a Covid-19 vaccine certificate, there are still people who do not have an ID number. The target number from BPS does not match the Public Health Center data. Company employees who take part in the implementation of the hybrid cooperation vaccine cannot get Covid-19 vaccination services at the Public Health Center because their data has been entered into PT's Pcare application Kimi Farma. The need for community engagement with Traditional and Religious Leaders, Smart People as Public Relations for health workers, the need for a mandatory policy to have a Covid-19 vaccine certificate as a condition for obtaining public services. Hybrid needs to be developed again to cover other sectors such as NGOs and informal organizations as well as carry out non-physical development, especially in the health sector